2011
DOI: 10.3758/s13428-011-0084-x
|View full text |Cite
|
Sign up to set email alerts
|

A study of kinematic cues and anticipatory performance in tennis using computational manipulation and computer graphics

Abstract: Computer graphics of digital human models can be used to display human motions as visual stimuli. This study presents our technique for manipulating human motion with a forward kinematics calculation without violating anatomical constraints. A motion modulation of the upper extremity was conducted by proportionally modulating the anatomical joint angular velocity calculated by motion analysis. The effect of this manipulation was examined in a tennis situation-that is, the receiver's performance of predicting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 26 publications
(24 reference statements)
1
22
1
Order By: Relevance
“…The test serve motions were created on the basis of a real player's performance, but the motion was computationally perturbed at the racket-arm. To create the test CG animation, motion analysis and motion perturbation were performed, followed by the CG rendering [30].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The test serve motions were created on the basis of a real player's performance, but the motion was computationally perturbed at the racket-arm. To create the test CG animation, motion analysis and motion perturbation were performed, followed by the CG rendering [30].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have introduced techniques for injecting modified local motions into an original gross motion, i.e., perturbation of motion. These have included spatial exaggeration [27], dynamic simulation and noise addition [28], decomposition by principal component analysis [16], [29], and the modulation of joint angular velocity [30], [31]. For instance, three tennis serves (flat, slice, and topspin) were spatially exaggerated and displayed using a polygon CG model, and the serve type was more accurately identified as the level of exaggeration increased [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been suggested that motor simulation improves the reading of action kinematics performed by others ( Aglioti et al, 2008 ; Urgesi et al, 2012 ; Mulligan and Hodges, 2014 ; Mulligan et al, 2016a , b ). It is well known that the superior prediction in skilled athletes is associated with better reading of kinematic information inherent in opponents’ actions ( Abernethy and Zawi, 2007 ; Abernethy et al, 2008 ; Huys et al, 2009 ; Ida et al, 2011 ). Indeed, Aglioti et al (2008) reported that expert basketball players could discriminate the outcome of free throws based on the kinematics of the model’s hand movements.…”
Section: Discussionmentioning
confidence: 99%
“…The forehand stroke in tennis is a rapid movement; therefore, the use of slow-motion footage should lead to the activation of the AON. Considering that skilled anticipatory judgments are underpinned by the detection of key kinematic cues from an opponent’s movements ( Jones and Miles, 1978 ; Shim et al, 2005 ; Abernethy and Zawi, 2007 ; Jackson and Mogan, 2007 ; Williams et al, 2009 ; Ida et al, 2011a , b ; Fukuhara et al, 2017 ), the prolonged time afforded to detect key kinematic cues from an opponent’s movements would lead to better anticipatory performance.…”
Section: Introductionmentioning
confidence: 99%